Governance of public schools in relation to employment of educators : a case study of selected schools in the Mopani District - Monyela, Gigigi Eunice (My University, 2022)
Employment of educators has never been such a problem as it is now where race and ethnicity are at the centre stage in the recruitment and appointment of educators. The high rate of unemployment and exorbitant cost of living in the country also worsen the situation. The problem of employment in public education is compounded by the semi-literate School Governing Bodies (SGB) especially in most disadvantage rural schools, who are expected to recommend the appointment of educators to the Head of the Department. Employment of educators remains a challenge in the Department of Education. This research study provides a critique and an analysis of the role played by the SGB in school governance as elucidated in the literature and also stated by the South African Schools Act 84 of 1996. The aim of the study is to ascertain the alignment of educators‟ employment policies to South African Schools in the Mopani District. The research also highlights the challenges that hinder effective governance and management such as lack of knowledge and skills, to interpret and implement policies and regulations when appointing relevant educators. The study reveals an unethical behaviour amongst principals and governing body of policy non-adherence that amounts to corruption within the public service. The dysfunctionality of governance and management to hire relevant, competent and qualified educators to occupy promotional posts cause more problems in the society as a whole, such as lack of accountability in terms of best education for the learners who are our future generation. The department should revise the roles and laws concerning school governors. The maladministration occurring in public institutions and schools is to be punished by law and public servants are to be accountable for their wrong actions taken. In conclusion the Public Service Act 103 of 1994, section 11 stipulates that filling of posts in the public service must be given a democratic values and must follow democratic principles. Appointments should be based on qualifications, skills and competences. Nevertheless educators are appointed into various positions through corrupt activities. This must come to an end for effective governance in education to prevail.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Educators; Employment; Head of Department; School governing bodies (SGB); Educators -- South Africa -- Limpopo; Public schools; Public schools -- Employees; School management teams